Improvement of edible crotalaria spp through artificial pollination - Wasonga, M.A; Arunga, E.E; Muli, J.K.; Budambula, N.L.M (UoEm, 2023)
Slender leaf (Crotalaria ochroleuca and Crotalaria brevidens) are indigenous leafy vegetables commonly cultivated in Kenya with high nutritive value and medicinal benefits. Despite the benefits of the vegetable it is grown and consumed only in some parts of the world and has been neglected in terms of research. Artificial pollination of any crop forms the basis of improvement however, there is limited information on the breeding of Crotalaria. The study aimed to cross two distinct species of Crotalaria using artificial pollination. Two landraces from two counties in Kenya were crossed in a completely randomized design set up within the greenhouse. A six-day-old flower bud of C. ochroleuca of, the female parent was emasculated. A fully opened flower of C. brevidens was used as a pollen source. The pollen was rubbed on the stigma of the female parent and inserted back into the keel petal. Data were collected on the total number of mature pods and seeds then subjected to analysis of variance. The artificial pollination cross of C. ochroleuca and C. brevidens showed a success rate of 75%. The time of crossing did not have significant effect on the success rate, pod and seed production. The rubbing method was the best method of artificial interspecific pollination of Crotalaria. Successful interspecies pollination is a foundation for the improvement of edible Crotalaria through hybridization
Keywords: Crotalaria; crop improvement; crop improvement; artificial pollination; rubbing method